Pemanfaatan Alat Peraga Dakota untuk Menguatkan Pemahaman Konsep Matematika Siswa - Marissa Yunita Azhari; Jelita; Fenny Anggreni (Lembaga Penelitian dan Pengabdian Masyarakat (LP2M) IAIN Langsa, 2021)
The purpose of this research is to find out how the students' mathematical understanding of the concepts before and after the use of the Dakota defense equipment and whether the Dakota defense apparatus affects the students' understanding of the mathematical concepts in MIS.Research of the quasi-experiment of the kind of Nonequivalent Control Group Design.In this study the sample used was a class IV A as an experimental group and a class IV as a control group with 15 students each. The sample was taken using a Simple Random Sampling technique with a method of drawing. Data were analyzed using percentages and T test, namely SPSS. The results showed that student’s understanding of mathematical concepts before and after using the Dakota teaching aids was increasing, this was evidenced by the percentage of understanding mathematical concepts before using the teaching aids was 34,33%, while after using the Dakota teaching aids the percentage of understanding mathematical concepts wa 80,6%. As for the t-test, it was 4,267 with a sig (2-tailed) of 0,000. Since sig got a < 0.05 so significantly then we can assume Ha accepted that there is an influence of Dakota's defense on the student's understanding of the mathematical concept at MIS Integrated Langsa